2022
DOI: 10.2174/1573403x18666220415150943
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Fetal Congenital Heart Defects

Abstract: Endothelial dysfunction, impaired implantation and placental insufficiency have been identified as mechanisms behind the development of pre-eclampsia, resulting in angiogenic factors’ alteration. Angiogenic imbalance is also associated with congenital heart defects, and this common physiologic pathway may explain the association between them and pre-eclampsia. This review aims to understand the physiology shared by these two entities and whether women with pre-eclampsia have an increased risk of fetal congenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…It is widely reported that abnormal angiogenesis in the placenta can lead to the development of not only FGR, but also maternal preeclampsia (PE) [ 2 ], due to impaired remodeling of maternal spiral arteries and placental under perfusion. However, in the last few years, various reports have suggested that placenta-related complications due to angiogenic imbalance may be associated with fetal cardiac remodeling and subclinical dysfunction [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], as well as a higher risk of congenital heart disease (CHD) [ 10 , 11 , 12 ]. These fetuses are then associated with poorer perinatal outcome, more prenatal death, severe intrapartum fetal distress, and perinatal brain injury [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that abnormal angiogenesis in the placenta can lead to the development of not only FGR, but also maternal preeclampsia (PE) [ 2 ], due to impaired remodeling of maternal spiral arteries and placental under perfusion. However, in the last few years, various reports have suggested that placenta-related complications due to angiogenic imbalance may be associated with fetal cardiac remodeling and subclinical dysfunction [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], as well as a higher risk of congenital heart disease (CHD) [ 10 , 11 , 12 ]. These fetuses are then associated with poorer perinatal outcome, more prenatal death, severe intrapartum fetal distress, and perinatal brain injury [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maldevelopment of the placenta is linked with a variety of serious pregnancy complications (e.g., preeclampsia, fetal growth restriction) that cause maternal and fetal illness or death 11 . Interestingly, these pregnancy complications are also associated with a higher incidence of CHDs, suggesting the notion of a shared developmental trajectory between the placenta and nascent heart gaining recognition as the "placenta-heart axis" 2,12 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that this condition often resolves completely within 12 weeks following childbirth [8,9]. A large body of epidemiological research suggests that placental defects are thought to be caused by abnormal immune reactions of the mother to invading trophoblast cells, and preeclampsia is associated with primiparity, partner change, and oocyte donation for assisted reproduction [10,11]. Although there is a wealth of literature supporting the immunological origins of preeclampsia, its specifc underlying biological mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%